A randomized controlled trial protocol assessing the effectiveness, safety and cost‐effectiveness of methotrexate vs. ciclosporin in the treatment of severe atopic eczema in children: the TREatment of severe Atopic eczema Trial (TREAT)4. (28th October 2018) - Irvine, A.D.; Jones, A.P.; Beattie, P.; Baron, S.; Browne, F.; Ashoor, F.; O'Neill, L.; Rosala‐Hallas, A.; Sach, T.; Spowart, C.; Taams, L.; Walker, C.; et al.
Summary: Background: Oral systemic immunomodulatory medication is regularly used off‐licence in children with severe atopic eczema. However, there is no firm evidence regarding the effectiveness, safety, cost‐effectiveness and impact on quality of life from an adequately powered randomized controlled trial (RCT) using systemic medication in children. Objectives: To assess whether there is a difference in the speed of onset, effectiveness, side‐effect profile and reduction in flares post‐treatment between ciclosporin (CyA) and methotrexate (MTX), and also the cost‐effectiveness of the drugs. Treatment impact on quality of life will also be examined in addition to whether FLG genotype influences treatment response. In addition, the trial studies the immune–metabolic effects of CyA and MTX. Methods: Multicentre, parallel group, assessor‐blind, pragmatic RCT of 36 weeks' duration with a 24‐week follow‐up period. In total, 102 children aged 2–16 years with moderate‐to‐severe atopic eczema, unresponsive to topical treatment will be randomized (1 : 1) to receive MTX (0·4 mg kg −1 per week) or CyA (4 mg kg −1 per day). Results: The trial has two primary outcomes: change from baseline to 12 weeks in Objective Severity Scoring of Atopic Dermatitis (o‐SCORAD) and time to first significant flare following treatment cessation. Conclusions: This trial addresses important therapeutic questions, highlighted in systematic reviews and treatment guidelines for atopic eczema. The trial design is pragmatic to reflect current clinical practice. Abstract : What's already known about this topic? Oral systemic immunomodulatory medication is regularly used off‐licence in children with severe atopic eczema. Ciclosporin is the commonest first‐line systemic agent used in this context, but methotrexate has emerged as an important therapeutic alternative. There is currently no adequately powered randomized controlled trial that compares both treatments in children. What does this study add? The TREatment of severe Atopic eczema Trial (TREAT) addresses this gap and compares the effectiveness, safety, cost‐effectiveness and impact on patient's quality of life of these two drugs. TREAT also examines the effects of both drugs using systemic and cutaneous markers of inflammation and the effect of filaggrin ( FLG ) genotype and T‐cell cytokine signatures on treatment response. Respond to this article Plain language summary available online